IL-1β Promotes a New Function of DNase I as a Transcription Factor for the Fas Receptor Gene - Thiyagarajan, Dhivya; Pedersen, Hege L.; Seredkina, Natalya; Horvei, Kjersti D.; Arranz, Lorena; Sonneveld, Ramon; Nijenhuis, Tom; van der Vlag, Johan; Rekvig, Ole P. (Frontiers in Cell and Developmental Biology, 2018)
Recently we described that endonuclease inactive DNase I translocated into the nucleus in response to increased endogenous IL-1β expression. Here, we demonstrate impact and function of translocated DNase I in tubular cells. Effect of cytokines on expression level and nuclear localisation of DNase I and corresponding levels of Fas receptor (FasR) and IL-1β were determined by confocal microscopy, qPCR and western blot analyses, in presence or absence of siRNA against IL-1β and DNase I mRNA. Nuclear DNase I bound to the FAS promotor region as determined by chromatin immuno-precipitation analysis. Data demonstrate that; (i) translocation of DNase I depended on endogenous de novo-expressed IL-1β, (ii) nuclear DNase I bound FAS DNA, (iii) FasR expression increased after translocation of DNase I, (iv) interaction of exogenous Fas ligand (FasL) with upregulated FasR induced apoptosis in human tubular cells stimulated with TNFα. Thus, translocated DNase I most probably binds the promoter region of the FAS gene and function as a transcription factor for FasR. In conclusion, DNase I not only executes chromatin degradation during apoptosis and necrosis, but also primes the cells for apoptosis by enhancing FasR expression.